(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Nanostructured Titanium dioxide were synthesized using two different deposition techniques: sol-gel and sputtering. Anatase structural phase of titania was observed for the samples synthesized by both methods by controlling tempeture. The scanning electron microscopy indicated that the average particle size of samples prepared by plasma sputtering was smaller than that of samples prepared sol-gel. The spectroscopic measurements confirmed the formation of Ti-O bonds. Energy band gap was determined and found to be 3.2 eV for sample prepared by sol-gel and 3.1 eV for samples prepared by plasma sputtering. These results highlight the advantages of plasma sputtering technique over sol-gel as thin film deposition methods.